The Disease Burden of Hereditary Angioedema: Insights from a Survey in French-Canadians from Quebec - Jean-Nicolas Boursiquot; Hugo Chapdelaine; Charles St-Pierre; Jacques Hébert (Journal of Immunology Research)
Background. Limited data are available on the clinical profile and disease burden of hereditary angioedema (HAE) in Canadians. Objective. This study aimed to assess HAE disease characteristics and the burden of disease in Canadians with HAE types I, II, and normal levels of C1 inhibitor (nC1-INH). Materials and Methods. A 46-item patient survey evaluating clinical characteristics and burden of disease was developed and disseminated by the HAE patient organization Angio-oédeme héréditaire du Québec in Quebec, Canada, from May 2019 to February 2020. The survey received Research Review Board ethics approval. Results. In the 35 respondents, HAE type I was the most common (46%), followed by nC1-INH (43%). Female participants were significantly younger at first symptom presentation than males (p=0.04). Prior to diagnosis, 69% of participants underwent unnecessary treatments and procedures, with a 10-year delay between first symptoms and diagnosis. Before starting the current treatment, 42% of participants experienced weekly HAE attacks. Most participants identified experiencing attacks in the abdomen (89%), followed by the larynx (66%), feet (66%), hands (63%), and face (63%). Most attacks were severe or moderate, yet almost half of patients waited >1 hr before getting medical attention at their last emergency department (ED) visit. HAE was associated with decreased health-related quality of life, leading to significant functional impairment in personal and professional life. As compared to HAE type I/II, patients with HAE nC1-INH were treated more often with tranexamic acid for long-term prophylaxis, and their condition was less controlled, resulting in more attacks and ED visits. Conclusion. HAE manifests in this patient population as frequent moderate-to-severe attacks and a high disease burden; the HAE subtype may differentially affect care requirements. There is an urgent need for increased awareness and education on HAE among treating physicians.